Leveraging technology for the survival of the restaurant business: a systematic literature review / Mohd Aliff Abdul Majid ... [et al.] - Abdul Majid, Mohd Aliff; Azman, Ana Batrisyia; Usman, Samsul Bahri; Zahari, Harnizam; Abdul Raji, Mohd Nazri (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The convergence of technology and the restaurant industry has become increasingly critical, especially in the context of the unprecedented challenges presented by the COVID-19 pandemic. Embracing technology has played a pivotal role in enabling restaurants not only to endure but also thrive in these turbulent times. This conceptual paper examines how technology has played a vital role in the survival and adaptation of restaurants during the COVID-19 pandemic. It highlights the importance of swift technology integration for restaurants to remain competitive and navigate the disruptions caused by the pandemic. The study emphasizes the significance of technology in ensuring the restaurant industry's continuity and proposes ongoing investments in technology for post-pandemic competitiveness. This research also explores the positive impact of technology on convenience, efficiency, and customer satisfaction in the foodservice sector, offering valuable insights for restaurant owners, policymakers, and technology developers. While acknowledging its limitations, this study underscores the need for further exploration of technology's role in the survival and success of small and medium-sized restaurants, especially in developing countries, as they strategize for sustainability amid the ongoing global health crisis.